A cross sectional study of lipid profile in stroke patients - C., Nirmala A.; S., Hrishikesh (International Journal of Advances in Medicine, 2020)
Background: Atherosclerosis affects multiple vascular beds, accounting for nearly all of coronary heart disease and some proportion of ischemic strokes. Serum lipid levels have an effect on the short-term mortality due to strokes. But in some studies, there was no dyslipidemia in patients who presented with acute stroke. It is important to evaluate the serum lipid levels in both the types of strokes to guide lipid lowering therapy which can reduce incidence of stroke and related mortality. This study is undertaken to evaluate the role of serum lipids in patients of stroke in our centre. Methods: It is a cross sectional study, conducted on 176 patients of stroke, who were assessed by NIHSS stroke scale clinically. Serum lipid profile was measured in all patients. Data was entered in Microsoft Excel and analysed by descriptive statistics. Chi Square test was used for association of qualitative variables. A p value<0.05 was considered statistically significant. Results: In this study conducted on 176 patients, LDL values were deranged more in CVA-bleed group compared to CVA-infarct group. BMI was the best anthropometric measure that correlated with LDL. LDL was also the most common parameter that was deranged in nonsmokers (61.8%) whereas in smokers, total cholesterol (66.3%) was most commonly deranged. Triglyceride and VLDL values were deranged more commonly in diabetic group than in non-diabetic group. A total of 123 out of 145patinets with CVA- infarct, had deranged lipid profile and among patients with CVA- bleed 24 out of 32 had deranged lipid profile. Conclusions: Results of this study shows significant derangement in lipid profile especially in LDL cholesterol levels in both infarct and bleed group, therefore starting statin therapy would prove to be beneficial in preventing recurrence of stroke.